Prevalence of blaTEM , blaSHV and blaCTX-M genes in clinical isolates of Escherichia coli and Klebsiella pneumoniae from Northeast India - Arijit Bora; Naba Kumar Hazarika; Sanket Kumar Shukla; Kashi N. Prasad; Jayanta Biswa Sarma; Giasuddin Ahmed (Wolters Kluwer Medknow Publications, 2014)
Aim: This study was carried out to determine the presence of blaTEM , blaSHV and blaCTX-M genes in extended-spectrum β-lactamase (ESBL) producing Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae) at a tertiary care referral hospital in Northeast India. Materials and Methods: A total of 270 E. coli and 219 K. pneumoniae isolates were recovered during the period between August 2009 and July 2010. Kirby-Bauer disk diffusion method was performed to determine the antibiotic resistance pattern. Screening and phenotypic confirmatory test for ESBL production were performed using standard disc diffusion methods. Each of the initial ESBL screening test isolate was investigated for the presence of blaTEM , blaSHV and blaCTX-M genes via polymerase chain reaction (PCR) using gene-specific primers. Results: Phenotypic confirmatory test able to detect ESBL production in 73.58% of E. coli and 67.24% of K. pneumoniae. However, PCR amplification showed the presence of one or more ESBL genes in each of the initial ESBL screening positive isolate. Among three ESBL genotypes, the most prevalent genotype was found to be blaCTX-M in E. coli (88.67%) and blaTEM in K. pneumoniae (77.58%) ESBL producing isolates. Majority of ESBL producing isolates possess more than one ESBL genes. Conclusion: This study constituted a primer report on high prevalence of blaTEM and blaCTX-M genes in ESBL producing isolates of E. coli and K. pneumoniae and denotes the need of more extensive studies on these antibiotic genes to determine the magnitude of the problem of antibiotic resistance exiting in this locality.